Effective syngas cleanup and reforming using Ni/ - Wang, Duo; Yuan, Wenqiao; Wei, Ji (International Journal of Agricultural and Biological Engineering, 2010)
This work reports the performance of a selective Ni-based catalyst in tar removal and syngas reforming. Benzene was used as the model tar to optimize catalytic reaction conditions. Parameters investigated were reaction temperature (700ºC to 900ºC), gas residence time (0.1 s to 1.1 s), and catalyst loadings (3% to 21% of the weight of γ-Al2O3 support). On the basis of the benzene test, a reaction temperature of 800ºC, catalyst loading of 15wt%, and residence time of 0.3 s were chosen as optimum reaction conditions. Testing of these conditions showed that the Ni/γ-Al2O3 catalyst removed more than 99% of tars in syngas in the downdraft gasifier and 98% in the updraft gasifier. Concentrations of combustible compounds of syngas also increased significantly. H2 concentration increased from 19.96% to 51.78% in the downdraft gasifier and from 23.97% to 37.39% in the updraft gasifier; CO concentration increased from 16.26% to 21.10% in the downdraft gasifier and from 22.95% to 25.64% in the updraft gasifier. The results indicate that the Ni/γ-Al2O3 catalyst and associated catalytic conditions could not only effectively eliminate tars but also improve the quality of syngas in biomass gasification. Key words: gasification, Ni/γ-Al2O3 catalyst, syngas reforming, tar removal DOI: 10.3965/j.issn.1934-6344.2010.02.039-045 Citation: Duo Wang, Wenqiao Yuan, Wei Ji. Effective syngas cleanup and reforming using Ni/γ-Al2O3 catalyst. Int J Agric & Biol Eng, 2010; 3(2): 39<span style="font-size: 9pt; line-height: 150%; font-family: